2005
DOI: 10.1128/jcm.43.9.4865-4867.2005
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Number Tandem Repeat Analysis of Meningococcal Isolates Belonging to the Sequence Type 162 Complex

Abstract: Thirty-one meningococcal isolates from carriers and disease cases belonging to the sequence type (ST) 162 complex, isolated in Greece in 1999 and 2000, were studied by the use of variable-number tandem repeat analysis. Our study demonstrated that the isolates belonging to the ST-162 clonal complex were a heterogeneous group. Based on this heterogeneity, it is unlikely that the disease-associated isolates represent an outbreak.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…It has been demonstrated previously that VNTR typing is capable of distinguishing among meningococcal isolates belonging to the ST‐32, ST‐11 and ST‐162 complexes [7,8]. The present results show that VNTR analysis can distinguish outbreak‐associated isolates from sporadic cases belonging to the same ST complex.…”
Section: Phenotypic and Genotypic Data For Neisseria Meningitidis Issupporting
confidence: 71%
See 1 more Smart Citation
“…It has been demonstrated previously that VNTR typing is capable of distinguishing among meningococcal isolates belonging to the ST‐32, ST‐11 and ST‐162 complexes [7,8]. The present results show that VNTR analysis can distinguish outbreak‐associated isolates from sporadic cases belonging to the same ST complex.…”
Section: Phenotypic and Genotypic Data For Neisseria Meningitidis Issupporting
confidence: 71%
“…Previous studies by Yazdankhah et al. [7,8] have shown that VNTR analysis can be used for fine typing of meningococcal isolates belonging to the same clonal complex, with genetic polymorphism within the sequence type (ST) ST‐11 and ST‐162 complex of N. meningitidis revealing that they are quite heterogeneous. As ST‐162, ST‐32 and closely related STs predominate among both disease‐associated and carrier isolates in Greece [9], the present study aimed to investigate the potential of the existing conventional and molecular techniques for the identification of outbreak‐associated isolates.…”
Section: Phenotypic and Genotypic Data For Neisseria Meningitidis Ismentioning
confidence: 99%
“…The relevance of this study is related to the high incidence, in Greece, of cc162, which is rare in Europe. cc162 has been described to be present both in disease-associated and in carrier isolates in Greece, with a high degree of heterogeneity among the isolates [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Yazdankhah et al presented two studies on the use of MLVA for molecular typing of N. meningitidis (37,39). In their reports, they show that their MLVA can be used for fine typing of meningococcal strains and that outbreaks can be delineated by VNTR analysis.…”
Section: Discussionmentioning
confidence: 99%
“…To type a single strain, seven PCRs and 14 sequence reactions are required. Recently, multiple-locus variable-number tandem repeat analysis (MLVA) has been introduced as a typing method for a large number of bacterial pathogens (6-8, 10, 16, 17, 19, 23, 26, 28, 29, 32, 34, 35) and meningococci (37,39). In MLVA, the variability in the numbers of short tandem repeated sequences is utilized to create DNA fingerprints for epidemiological studies.…”
mentioning
confidence: 99%